Promoting self-esteem in the child for a good socioemotional development - Elguera Martinez, Marlene (2019)
In the present article we want to contribute with a very important issue for the well-being of children; and it is the self-esteem, that we know that without it no human being is capable of moving forward. It is needed to have a healthy self-esteem in order to accept ourselves and accept others, so we acquire socio-emotional skills that will help us to control our emotions and get along with others.